Analysis of HIV-1 subtypes and drug resistance mutations in people who inject drugs in Aizawl and nearby districts of Mizoram, India - Komal Raskar; Lal Thlengliani; Andrew Lalbiaknunga; Dipali Kale; Ajit Patil; Pragati Chavan; Richard CLR Hluna; Samiran Panda; Swarali Kurle (Virulence)
Over the last decade, there has been a steady increase in HIV-1 prevalence in Mizoram, India. Importantly, this increase in HIV-1 prevalence is not only limited to the key population groups such as female sex workers (FSWs) or people who inject drugs (PWID), and has been witnessed in general population as well. Injecting drug use has long been one of the key drivers of HIV-1 epidemic across the north-eastern states of India. In this study, using HIV-1 pol gene region sequences from Aizawl and adjoining districts, we examined the HIV-1 subtypes, recombinant forms, drug resistance mutations and also the spatiotemporal dynamics of the potential unique recombinant forms. In our dataset, the dominant subtype was HIV-1 subtype C (94.91%). We could also identify the presence of CRF01_AE (1.69%) and BC recombinant forms (3.39%). Drug resistance mutation analysis revealed that resistance against non-nucleoside reverse transcriptase inhibitors was most common in the sequences having any resistance mutations. Evolutionary analysis of unique BC recombinants estimated the most recent common ancestor of these sequences around 2004–2005 and them having an ancestry of United States of America (USA) origin.